AUDITING NETWORK SECURITY IN REMOTE WORK ENVIRONMENTS: A BIBLIOMETRIC REVIEW - Costa, Filipe; Dias Lousã, Mário Jorge; Dias Lousã, Mário Jorge; Pereira de Morais, José Carlos; Pereira de Morais, José Carlos (ISPGAYA, 2026)
The remote work trend has changed the organizational network architectures of firms, thereby in-creasing the attack surfaces in cybersecurity and auditing. It has thus become increasingly important to understand security controls, risk management practices, and how audit mechanisms are imple-mented in distributed environments. This research employs a bibliometric review, conducted in ac-cordance with the PRISMA protocol, along with a qualitative interpretative analysis to understand scientific literature on cybersecurity, network security, and auditing in remote work contexts. The Lens database was used to collect metadata for publications from 2019 to 2025, which led to a dataset of 1,868 documents. After screening and eligibility assessment, 1868 documents were included in the final bibliometric and qualitative synthesis. The results show a significant increase in research output after 2020, associated with the global expansion of remote work. The analysis also highlights gaps related to remote auditing automation and monitoring in unmanaged environments. Overall, the results underscore the strengthening of technical security measures that are closely aligned with the ongoing gaps in auditing practices, thus indicating key areas for further research and the development of professional practice.
Keywords: Compliance Monitoring; Continuous Auditing; Cybersecurity Frameworks; Endpoint Security; Zero Trust Architecture.